Delays in Public Goods - Santanu Chatterjee; Olaf Posch; Dennis Wesselbaum (Center for Economic Studies and ifo Institute (CESifo), 2017)
In this paper, we analyze the consequences of delays and cost overruns typically associated with the provision of public infrastructure in the context of a growing economy. Our results indicate that uncertainty about the arrival of public capital can more than offset its positive spillovers for private-sector productivity. In a decentralized economy, unanticipated delays in the provision of public capital generate too much consumption and too little private investment relative to the first-best optimum. The characterization of the first-best optimum is also affected: facing delays in the arrival of public goods, a social planner allocates more resources to private investment and less to consumption relative to the first-best outcome in the canonical model (without delays). The presence of delays also lowers equilibrium growth, and leads to a diverging growth path relative to that implied by the canonical model. This suggests that delays in public capital provision may be a potential determinant of cross-country differences in income and economic growth.
Keywords: C61; E62; H41; O41; 330; public goods; delays; time overrun; cost overrun; implementation lags; fiscal policy; economic growth